Pengaruh Promosi Digital Marketing Dan Word Of Mouth terhadap Keputusan Konsumen Dalam Memilih Jasa Wedding Organizer Siapnikah.Id - Ulfi Maranisya; Reza Ardian Putra (Pusat Riset dan Inovasi Nasional, 2024)
This research was carried out at Siapnikah.Id which is located in Pancoran Mas Depok. Researchers are interested in conducting research to find out whether digital marketing and Word of Mouthinfluence consumer decisions in choosing WO Siapnikah.Id services. Therefore, it is important to understand how digital marketing and Word of Mouthcan achieve the goal of consumer satisfaction in finding wedding organizer services. This research uses a descriptive quantitative research method with a survey approach. The population in this research is wedding organizer consumers totaling 47 people. The sample for this research was determined using numerical data which was processed using statistics. The technique used for data collection is a questionnaire or questionnaire. In the research, 2 independent variables are used, namely digital marketing (X1), Word of Mouth(X2). The dependent variable used in this research is consumer decision (Y). The results of this research are that digital marketing and Word of Mouthget different data, where digital marketing has a significant and influential effect on consumer decisions, while Word of Mouthhas no influence and is not significant on consumer decisions in choosing Siapnikah.Id wedding organizer services.